Design and Fabrication of Blood Purification Device from Bacteria and Viruses - Madlol, Fatima Naeem (American Journal of Biology and Natural Sciences, 2024)
The current work deals with the relationship of wavelengths of visible light with blood and bacteria. We have designed a device that deals with wavelengths such as (red, blue, white, yellow (solar), ultraviolet rays) and their relationship to blood and bacteria. Random blood samples and it was found that it takes a long time in order to obtain reliable results, in addition to that it needs many medical procedures and facilities. We decided to develop the device and add a source of ultraviolet rays, the efficiency of ultraviolet radiation was tested in killing some types of bacteria such as (Staphylococcus aureus, Klebsiella, Proteus mirabilis), which They cause diseases to humans and other living organisms.